Peculiarities of the formation of homogenized images by plane-focusing Fresnel lenses - Петров, В. В.; Антонов, Є. Є.; Зенін, В. М.; Манько, Д. Ю.; Шанойло, С. М. (Інститут проблем реєстрації інформації НАН України, 2023)
An algorithm for simulating Fresnel microprism concentrator lenses, which forms a homogeneous image of the transmitted light rays in the focal plane, has been developed. Such flat-focusing lenses make it possible to form an optimal signal in systems of automatic control of moving objects with four-plane photodetectors, and are also promising for use in solar photovoltaic modules. Some samples of such specified focusing microprism devices with illumination distribution of the light spot in the form of circle and ring, were made by the method of diamond microcutting technique according to our simulation results. A feature of focusing structures created by the diamond cutting technique is a discrete change in the refractive angles of microprismatic zones, resulting in the discreteness of the images formed in the focus. This is a main difference from Fresnel focusing optics with aspherical convex circular surfaces, when the angles of refraction change continuously. In the manufacture of such new devices by the diamond cutting method it is possible to obtain almost mirror working surfaces of a high optical quality. However, the size of such conical refracting zones should not be too large to reduce the discreteness of the formed images, so the new specified focusing microprisms are made from several totally identical prismatic elements. With the help of collimated «green» laser beam, some samples of specialized transforming microprism structures were experimentally investigated, that form the uniform illumination of a light spot in the form of a light circle and a circle with a ring. Using computer modelling, the profiles of transmitted light rays were found, which made it possible to identify the reasons for the additional expansion of refracted light beams.